Peacemaker - Nourse, Alan Edward, 1928-1992; Ebel, Alex, 1932-2013 (Salt Lake City, UT : Project Gutenberg, 2022)
"Peacemaker" by Alan Edward Nourse is a science fiction novel written in the early 1950s. The story revolves around a character named Flicker, who is human and has embarked on a mission to communicate with an alien species that poses a threat to his people. The book explores themes of misunderstanding, the desire for peaceful communication, and the instinct for survival when faced with hostile forces. In "Peacemaker," Flicker is captured aboard an alien spaceship, where he learns that the aliens view him as a threat and consider killing him to ensure their safety. Despite their initial aggression, Flicker seeks a way to establish contact and convey critical messages to the aliens, warning them against encroaching on his people. Throughout the narrative, he navigates the challenges of captivity, using his cunning to exploit the aliens' weaknesses and ultimately engendering a deadly game of survival in the darkened confines of the ship. As tensions escalate, Flicker is forced to resort to violence, blurring the line between his original intentions as a peacemaker and the brutal reality of self-preservation, leading him to contemplate the balance between coexistence and defense against aggression. (This is an automatically generated summary.)
Release date is 2022-08-14
Greg Weeks, Mary Meehan and the Online Distributed Proofreading Team at http://www.pgdp.net
Keywords: Science fiction; Short stories; Extraterrestrial beings -- Fiction; Space ships -- Fiction; Human-alien encounters -- Fiction